Retinal Vasculitis in a Patient with Ankylosing Spondylitis: A rare Association - Majumder, Anindya Kishore; Roy, Rupak; Kharel Sitaula, Ranju; Magesan, Kowsigan; Majumder, Parthopratim Dutta (Nepalese Journal of Ophthalmology, 2018)
Purpose: To report a case of retinal vasculitis in a patient with ankylosing spondylitis. Background: Posterior segment involvement in HLA B-27-associated uveitis is uncommon but we report a case wherein retinal vasculitis was associated with HLA-B 27 uveitis. Case: A 36-year-old male, a diagnosed case of ankylosing spondylitis, presented to us with severe anterior segment inflammation associated vitritis in both the eyes. He received topical, oral steroid and immunosuppressive and 3½-month after the control of his uveitis, he underwent cataract surgery in his left eye. Fundus evaluation following cataract surgery revealed sclerosed retinal vessels and wide-field fundus fluorescein angiography confirmed retinal vascular involvement in both the eyes. Conclusion: Retinal vasculitis, though rare can occur in patients with ankylosing spondylitis especially in conditions which present with panuveitis-like picture.